Enhancing it support with knowledge management: knowledge management maturity level assessment at bph migas - Priyo Sambodo, Wisnu; Saksono, Prasetyo B. (The Indonesian Journal of Business Administration, 2018)
Abstract - According to IT blueprint, the development of knowledge management is planned to begin in 2018 and is expected to be completed by the end of 2018. However, the unavailability of the road map for the KM implementation plan has resulted in the organization lacking guidelines for strategizing, designing, developing and implementing KM initiatives. Knowledge Management (KM) is an effort to improve knowledge that is beneficial to the organization. BPH Migas as a regulator that produces regulations required by stakeholders should maximize its ability to effectively utilize its knowledge resources in order to be able to make decisions quickly and effectively. Implementing knowledge management can help BPH Migas become more productive, innovative, efficient and more adaptable to the ever-changing business environment. Implementation of KM is influenced by critical factors. Identifying the critical factors will facilitate and simplify monitoring to focus on some key areas that are considered important. The purposes of the study are to identify the critical factors affecting the successful implementation of KM, determine the current situation in terms of KM and use the identified factors to improve knowledge management implementation plans at BPH Migas. Researcher uses the General Knowledge Management Maturity Model (G – KMMM) framework as a model to measure the level of knowledge management maturity, which consists of 3 (three) categories of measurement ie people, process and technology. The research findings showed that the maturity level of BPH Migas was at the Defined level. It means that BPH Migas has the basic infrastructure to support KM implementation and run KM as part of its activitiesKeywords: G - KMMM, knowledge, knowledge management, maturity, knowledge management maturity level